1993
DOI: 10.1139/t93-049
|View full text |Cite
|
Sign up to set email alerts
|

Collapse behavior of sand

Abstract: Loose cohesionless materials can collapse during either static or dynamic loading, resulting in a rapid buildup of pore pressure and associated reduction in shear resistance. As the cohesionless material collapses, it rapidly looses resistance until the acting shear stress decreases to the available residual or steady-state strength. Specially designed stress-path testing has been performed on sand to investigate this collapse process. Results from this test program and previously published data show that a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(64 citation statements)
references
References 0 publications
9
52
0
Order By: Relevance
“…We observed that the void ratio of these samples deviated by less than ±0.6 % (±0.005) from the average void ratio of the specimen. This is consistent with the void ratio variations of undercompacted moisttamped specimens found by Sasitharan (1994).…”
Section: Specimen Preparationsupporting
confidence: 91%
“…We observed that the void ratio of these samples deviated by less than ±0.6 % (±0.005) from the average void ratio of the specimen. This is consistent with the void ratio variations of undercompacted moisttamped specimens found by Sasitharan (1994).…”
Section: Specimen Preparationsupporting
confidence: 91%
“…Chern (1983) [16], Kramer and Seed (1988) [17], Vasquez-Herrera and Dobry (1989) [18], Lade (1992) [19], (1993) [20], Ishihara (1993) [21], Konrad (1993) [22], Sasitharan et al (1993) [23], (1994) [24] and among others) identified similar yield conditions and proposed various names for these conditions. The collapse line is considered as a limit state boundary between the stable and the unstable states of soil undrained behaviour.…”
Section: Undrainedmentioning
confidence: 99%
“…For example, during water infiltration, a soil element in a slope may follow a CSD stress path, as suggested by Brand (1981). Along this stress path, a soil element may become unstable under fully drained conditions (Sasitharan et al, 1993;Skopek et al, 1994;Anderson & Riemer, 1995;Anderson & Sitar, 1995;Chu et al, 2003;Leong, 2004;Loke, 2004;Wanatowski, 2005;Wanatowski et al, 2010).…”
Section: Instability Under Drained Conditionsmentioning
confidence: 99%
“…Therefore, as suggested by Brand (1981) when investigating the failure mechanisms of a slope, the stress-strain behaviour of the soil along stress paths that simulate water infiltration should be studied. Such stress paths may be idealised as paths with constant shear stress, but decreasing mean effective stress, or the so-called constant shear drained (CSD) tests performed under constant deviatoric stress (Brand, 1981;Sasitharan et al, 1993;Skopek et al, 1994;Anderson & Riemer, 1995;Anderson & Sitar, 1995;Chu et al, 2003;Orense et al, 2004;Daouadji et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation